2013
DOI: 10.2967/jnumed.112.112169
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Radiotherapy of Prostate Cancer with a Gastrin-Releasing Peptide Receptor Antagonist Is Effective as Monotherapy and in Combination with Rapamycin

Abstract: The gastrin-releasing peptide receptor (GRPr) is overexpressed in prostate cancer and is an attractive target for radionuclide therapy. In addition, inhibition of the protein kinase mammalian target of rapamycin (mTOR) has been shown to sensitize various cancer cells to the effects of radiotherapy. Methods: To determine the effect of treatment with rapamycin and radiotherapy with a novel 177 Lu-labeled GRPr antagonist ( 177 Lu-RM2, BAY 1017858) alone and in combination, in vitro and in vivo studies were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 36 publications
7
71
0
Order By: Relevance
“…Up to now, GRP-R-based PRRT has been performed targeting prostate cancer, either in xenograft-bearing animals, with GRP-R agonists or antagonists (14,34), or in patients during a pilot study using 177 Lu-AMBA (24). However, GRP-R-based PRRT is not yet being applied in BC animal models or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, GRP-R-based PRRT has been performed targeting prostate cancer, either in xenograft-bearing animals, with GRP-R agonists or antagonists (14,34), or in patients during a pilot study using 177 Lu-AMBA (24). However, GRP-R-based PRRT is not yet being applied in BC animal models or patients.…”
Section: Discussionmentioning
confidence: 99%
“…177 Lu-GRPR antagonists have not been tested in clinical studies thus far, even though they have shown promising results in preclinical studies (15). Radionuclide therapy using PSMA-targeted tracers has been more widely explored, as PSMA expression has been validated in advanced prostate cancer in several reports.…”
Section: Improving Pharmacokinetics and In Vivo Stabilitymentioning
confidence: 99%
“…Variability in toxicity, response, and organ dose has been identified but not yet entirely explained. Methods to account for these variabilities and accurately estimate delivered activity are under investigation, including the use of 111 In-based organ dosimetry (31).…”
Section: A Nuclear Medicine Physician Perspectivementioning
confidence: 99%
“…Somatostatin receptors in NETs, particularly in carcinoids and gastroenteropancreatic tumors, were discussed with emphasis on the use of 111 In, 90 Y, and 177 Lu labels and theranostic agents. Somatostatin receptors, including the 5 subtypes (1, 2a and 2b, 3, 4, and 5) have been well described in the literature, and numerous studies have reported on the characteristics and affinities of radiolabeled somatostatin analogs, including 111 In-DTPA-octreotide (Octreoscan; Mallinckrodt Pharmaceuticals), 90 (86,87).…”
Section: Targeted Radionuclide Therapy • Fahey Et Almentioning
confidence: 99%
See 1 more Smart Citation